Decentralization as a Basis for Modernisation of Public Administration: European Experience for Ukraine - Pukhkal, Oleksandr; Karlova, Valentyna; Reiterovych, Ihor; Sytnyk, Svitlana; Tyutyunnik, Ivan (International Journal of Criminology and Sociology, 2021)
Ensuring the development of Ukraine as a sovereign and independent, democratic, social, and legal state at the present stage requires, first of all, the establishment of an effective domestic system of public administration. The purpose of the paper is to analyse the modernisation of public administration in European countries. The analysis revealed the specific features of modernisation of public administration at the regional level, typical of the unitary countries of the European Union, close to Ukraine in terms of territorial, demographic, administrative-territorial structure, and other criteria. In particular, the authors explored the features of public administration reforms in France and Poland. Also, steps were identified to intensify modernisation of public administration at the regional level in Ukraine under decentralisation in the context of the experience of European countries. Upon substantiating the results of the study, authors concluded that the adaptation of modernisation of the European experience should take the obvious shortcomings into consideration so as not to exacerbate the problems of relations between different levels of public authority in the regions of Ukraine, which are already familiar to Ukrainian realities.